Comprehensive paleodemographic study of the Koshkeldinsky 2 burial ground (Chechen Republic). - Boruckaa, Svetlana Borisovna; Ahmarov, Azamat Usmanovic; Vasil'ev, Sergej Vladimirovic; Frizen, Sergej Ur'evic (History, Archeology and Ethnography of the Caucasus, 2026)
A paleodemographic study was conducted of the group that left the Koshkeldinsky 2 burial ground in the Gudermes district of the Chechen Republic, which is an old abandoned Muslim cemetery, approximately dates back to the 17th – first half of the 19th centuries. In 237 burials, 243 skeletons were found, determined by age and, for adults, also by sex. A comparative analysis was conducted. The peak mortality in the group falls on the first age cohort of 0-5 years, as well as in all the Caucasian groups we studied. The peak mortality of adult men and women falls on the final age cohort of 50+ years. In terms of the peak mortality in the group as a whole, the peaks of mortality of men and women, the group from the Koshkeldinsky burial ground is most similar to the groups from the Zmeysky burial ground (North Ossetia) and Krasnogorsk XIIb (Karachay-Cherkessia).The average life expectancy in the group from the Koshkeldinsky 2 burial ground is extremely low. In this regard, the group turned out to be closest to the Krasnogorskoye XIIb group (Karachay-Cherkessia). The percentage of infant mortality in the group from the Koshkeldinsky 2 burial ground turned out to be very high, 60.08%, the highest among the studied groups. Moreover, a third of the children died as newborns. The infant mortality rate indicates demographic disadvantage in the group. The group from Koshkeldy turned out to be closest to the Krasnogorskoye XIIb group (Karachay-Cherkessia) in this indicator.There were approximately 13% more adult men in the group than women. In all the studied groups, there were more men than women to one degree or another. The final age cohort (50+ years) in the group from the Koshkeldinsky 2 burial ground is not very representative, unlike, for example, the group from the Zmeysky burial ground. The majority of the final age group were men. At the same time, adult men and women in this age cohort show a peak in mortality, as well as in the groups from the Zmeysky burial ground and the Krasnogorskoye XIIb burial ground.
Keywords: Paleodemography; age cohort; paleodemographic indices; average life expectancy; infant mortality; final age cohort.